Data acquisition system / Abd Wahab Husin and Omar Ahmad - Husin, Abd. Wahab; Ahmad, Omar (1986)
The project was the brainchild of En. Ahmad Fauzi Ibrahim. The authors designed their own hardware and software under strict supervision of the project supervisor. Some materials were adapted from relevant texts and numerous individuals were consulted.